Parallel simulation of dense two-dimensional polymer systems - Forrest, Bruce M.; Baumgärtner, Artur; Heermann, Dieter W. (Computer physics communications, 1989)
We present a parallel algorithm for the simulation of dense lattice polymer systems. The algorithm will be given for a two-dimensional system although the algorithm can be generalized to higher dimensions. We discuss timing results and applications.